Keselarasan Tafsir Taisirul at-Tafsir dengan Perkembangan Zaman: Menyingkap Relevansi dan Adaptasi Penafsiran Al-Qur'an di Era Modern - Pratama, Fingki; Pathurrahman (STIQ al-Lathifiyyah Palembang, 2024)
This research aims to examine the alignment of Tafsir Taisirul at-Tafsir with modern developments, revealing the relevance and adaptation of the interpretation of the Qur'an in the contemporary era. The research method used is a qualitative approach, including text analysis and literature study. Text analysis is carried out in depth on Tafsir Taisirul at-Tafsir to understand the meaning, symbolism, and context of interpretation given by the author. Literature studies are conducted by collecting secondary data from related literature, including other Qur'anic commentaries, academic articles, books, and journals. Historical methods are used to trace the social, cultural, and intellectual backgrounds that influence interpretation, while sociological methods are applied to analyze the social and cultural context of the present. The literary method is used to identify symbolism and implicit meaning in interpretation. The results of the study show that Tafsir Taisirul at-Tafsir has a good alignment with the development of modern times. The contextual approach used allows this interpretation to remain relevant to contemporary issues, such as technology, human rights, and changing social values. The use of symbolism and implicit meaning in tafsir also provides depth of meaning and allows for deeper reflection on religious teachings. This research makes a valuable contribution in understanding the relevance and adaptation of Tafsir Taisirul at-Tafsir in modern developments and shows the importance of a multidisciplinary approach in the interpretation of the Qur'an.